The Urgency of Character Education from the Perspective of KH. Hasyim Asy’ari for Generation Z - Hamidah Hamidah; Mohamad Salik; Mohammad Fahmi; Atika Agustina Tarik; Mas Ayu Ainun Nisa (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2024)
This research aims to understand character education from the perspective of KH. Hasyim Asyi’ari for Generation Z as found in the book Adabul Alim Wa Mutaalim, by considering the achievement of seven values contained in character education for teachers for Generation Z and character education for Generation Z. The development of the times has led to an increase in moral degradation, which can hinder growth and become an issue in achieving the nation's ideals. This research falls under the category of library research, and the data analysis used in this study is content analysis, which aims to conclude an effort to identify message characteristics, conducted objectively and systematically. The results of this study indicate that there are seven aspects, namely purifying intentions, patience, contentment, asceticism, humility, piety, and avoiding filth and immorality, which when viewed from the perspective of character education by KH. Hasyim Asy'ari can be well achieved for Generation Z.